Pengaruh Kualitas Pelayanan, Cita Rasa, dan Harga terhadap Kepuasan Konsumen pada Restoran HokBen Atrium - Alifah Dikha Arianto; Purwatiningsih (Jurnal Manajemen Bisnis Digital Terkini, 2025)
HokBen, previously known as Hoka Hoka Bento, is a fast-food restaurant offering Japanese-style menus and has successfully built a strong brand in Indonesia since 1985. This study aims to analyze and explain the influence of service quality, taste, and price on customer satisfaction at the HokBen Atrium restaurant. This research uses a descriptive quantitative approach with purposive sampling technique, involving 100 respondents who are customers visiting and purchasing products at the HokBen Atrium restaurant. Data were collected using scale range analysis and path analysis, conducted with the help of Microsoft Excel and SPSS version 23. The results of the study indicate that service quality, taste, and price have a significant simultaneous impact on customer satisfaction. The coefficient of determination shows that these three variables account for 78.0% of the influence on customer satisfaction at the HokBen Atrium restaurant. The most dominant factor influencing customer satisfaction is taste, with the highest t-value of 5.279. This suggests that taste is the most important factor affecting customer satisfaction at the HokBen Atrium restaurant. This study provides valuable insights for the management of HokBen to further improve service quality, taste, and price adjustments to maintain and increase customer satisfaction levels.